Repair Strategies in English Literature Lectures in a University in Indonesia - Akhyar Rido; Heri Kuswoyo; Ayu Sumarni Suryaningsih; Sandi Nuansa; Ramelia Ayu; Rama Putra Arivia (TEKNOSASTIK, 2021)
This study was an attempt to investigate types and functions of repair strategies used by lecturers in English literature lectures in a university in Indonesia. Rido’s conceptual framework of repair strategies (2018) was used. Qualitative method was applied while the data were collected through video recording of three English literature lectures, comprising prose, drama, and literary criticism. The findings showed that the lecturers repaired both the linguistic (grammatical and pronunciation errors) and content-related aspects of the students while they were giving oral responses and making presentations. Therefore, the lecturers employed four types of repair strategies such as indicating an error has been made and correcting it, asking students to make self-repairs, indicating an error has been made and getting other students to correct it, and repeating students’ responses with changes. The functions of those repair strategies were to show the lecturers as role model and reliable source of knowledge, to give good examples, to make students think critically, to give opportunity for students to share ideas, and make students not aware they were being corrected so that they kept learning. The findings offer some implications for pedagogical considerations within university lecture, especially in English as a foreign language (EFL) setting.